Development of two loop-mediated isothermal amplification (LAMP) genomics-informed diagnostic protocols for rapid detection of Pantoea species on rice - Kini, K.; Wonni, I.; Silué, D.; Koebnik, R. (2021)
At least three species of Pantoea are responsible for bacterial blight disease and grain discoloration of rice in Sub-Saharan Africa. Thus, measures need to be taken to limit the pathogens' dispersion and robust diagnostic tools are required for rapid and cheap diagnosis in the field as well as for routine seed certification or control. Therefore, several diagnostic tools such as simplex and multiplex PCR schemes and a semi-selective medium have been developed and are being used. However, the use of these tools is time-consuming, expensive and therefore limited to laboratories that can afford the chemicals. We have therefore developed two isothermal loop amplification (LAMP) protocols, one of which detects all Pantoea species in the genus and another one that is specific for P. ananatis. • The novel LAMP assays allow rapid and sensitive detection of these bacteria.